Surgeon-performed ultrasound for preoperative localization in renal hyperparathyroidism patients - Mahno, Noor Ezmas; Abdullah Suhaimi, Sharun Niza; Lai, J Hai; Md Latar, Nani Harlina; Muhammad, Rohaizak (Jaypee Brothers Medical Publishers (P) Ltd, 2020)
Purpose/Introduction: Parathyroid surgery for renal hyperparathyroidism (RHPT) is indicated when patients have a progressive disease despite optimal medical therapy. An ectopic or an extranumerary parathyroid gland (PTG) is an obstacle to a successful total parathyroidectomy. Recently, surgeon-performed ultrasound (SPU) has been increasingly used for the preoperative localization of PTGs. Thus, we conducted a prospective observational single-center study to determine the accuracy of SPU for PTG localization in RHPT and the factors affecting its accuracy. Materials and methods: This is a prospective, observational, single-center study conducted in University Kebangsaan Malaysia Medical Centre between March 2018 and March 2019. The patients’ preoperative demography, clinical data, and relevant blood laboratory results, including calcium, phosphate, alkaline phosphatase, and intact parathyroid hormone, were recorded. Preoperative USG and surgery were performed by the same endocrine surgery consultant. Results: Surgeon-performed ultrasound localization had an overall accuracy of 78.1%, sensitivity of 81.0%, and specificity of 30.0% with a positive predictive value of 94.8% and a negative predictive value of 10.5%. The SPU gland localization rate was significantly higher in patients without goiter (median = 0.88, IQR = 0.63–1.00) than in those with goiter (median = 0.50, IQR = 0.25–0.75) (p = 0.028). Conclusion: Surgeon-performed ultrasound localization of the PTG in RHPT had an accuracy comparable with that in previous literature with the additional advantage of identifying concurrent unknown thyroid nodules. Considering the high prevalence of concomitant nodular thyroid disease in our RHPT population, we advocate the routine use of preoperative neck ultrasound for RHPT patients undergoing parathyroid surgery